?EVALUATION OF DIFFERENT RICE GENOTYPES FOR STABILITY IN YIELD PERFORMANCE (Biological Sciences - PJSIR, 2000)
The stability analysis of variance for six rice genotypes, tested across environments, indicated that the genetic differencesamongricegenotypesweresignificantat5%levelofprobability. Genotypesxlocationinteractionwasnon- significant. The regression coefficients (b) and small deviations from regression (82)of the genotypes Pak-4554 and Basmati-385 were found to be non-significant. The latter was significant for all genotypes except Pak-4554 and Basmati-385.Basmati-385performed almostbetteratalllocations.Therefore,theidealricegenotypewasBasmati-385 which showed average stableresults.